The Impact of Economic Policy Uncertainty on Business Transaction Credit Supply - Zhang Jiangxia (International Business Education Journal, 2023)
Based on the China Economic Policy Uncertainty (EPU) Index, this study uses quarterly data of listed companies from 2003 to 2022 to examine how economic policy uncertainty affects corporate commercial credit supply decisions. This report mainly uses simple OLS regression method and fixed effects OLS to study the impact of EPU on commercial credit supply. The results indicate that an increase in EPU will significantly reduce the commercial transaction credit provided by companies. After eliminating the impact of time and industry, EPU has a more significant impact on the credit supply of commercial transactions. Thus, for policy makers, it is necessary to maintain the stability of economic policies as much as possible and, if necessary, supplement corresponding supporting measures to alleviate the adverse effects of EPU.